Effectiveness Of Hypertension Exercise And Health Education On Decreasing Blood Pressure - Sri Wahyuni Adriani; Yuyus Febysna Feronika; Cindhy Ayu Meillani; Silvia Lestari; Dodik Dwi Hadiansah (Jurnal Kesehatan dr. Soebandi, 2021)
Introduction: Hypertension is a global health problem, due to its high frequency of occurrence and high risk of developing heart and blood vessel disease. One of the efforts or interventions to control high blood pressure in the community is to provide health education about controlling high blood pressure, and high blood pressure exercise to reduce blood pressure. Objective: To determine the effectiveness of providing health education and hypertension exercise in reducing blood pressure in patients with hypertension. Methods: Pre-experimental with one-group pre-post test design. The sample in this study was an adult community with hypertension, a total of 42 respondents were taken using simple random sampling. The statistical test used a paired sample t test with a value of = 0.05. Results: 54.8% of public knowledge related to hypertension had increased, 50.0% of public attitudes related to hypertension had increased, 71.4% of people's blood pressure with hypertension had decreased and p value = 0.000. Conclusion: Health education and hypertension exercise can reduce blood pressure in hypertensive patients. It is expected that nurses can provide health education and teach hypertension exercise to reduce blood pressure in hypertensive patients.